Optimization Guidance and Counseling by Bhabinkamtibmas in Prevention Ordinary Theft at Mojosongo Police - Keinard Akbar Khan Khan (Tanggon Kosala, 2021)
The crime of ordinary theft is an act of a person to take someone else's property that does not belong to him, it is regulated in Article 362 of the Criminal Code. Based on the data, the number of ordinary thefts in the Mojosongo District area is still high, so it is still necessary to optimize prevention efforts by Bhabinkamtibmas through coaching and counseling. This writing uses a qualitative writing approach with a type of analytical descriptive research. The focus of research is on coaching and counseling activities carried out by Bhabinkamtibmas in the jurisdiction of the Mojosongo Police Station.Data sources are primary and secondary data sources with data collection techniques through interviews, observations and document studies. Furthermore, data analysis techniques are used by reducing data, presenting data and drawing conclusions. The coaching and counseling activities carried out by the Mojosongo Police Bhabinkamtibmas have not been good enough which starts from the planning process that the administration is not complete before carrying out activities, organizing with a lack of personnel, the implementation stage in the field in providing counseling to the community, to the control stage from superiors to members. Based on the facts found, the final result of this writing shows that the existing management system can still be optimized for the better, then also optimize efforts to approach crime prevention to the community by the Bhabinkamtibmas of Mojosongo Sector Police when conducting counseling. Therefore, it is expected that the activity management system implemented and the crime prevention approach can be improved and maximized.